E-Learning is Effectively Used for Leadership Courses at Metamedia Universities - Maulana, Ilham Tri; Muhammad Giatman; Hasan Maksum (Journal International Inspire Education Technology, 2024)
This development research aims to develop learning media (E-Learning) in all courses at Metamedia University. E-Learning is designed to improve student learning outcomes, so students can fully understand the material provided. This study uses the Instructional Development Institute development method. IDI procedures are defining, developing, and evaluating. The type of data is primary data where the data obtained from media experts, lecturers and students. Data were analysed using Descriptive Data Analysis Techniques which describe the validity, practicality, and effectiveness of using E-Learning. The results obtained from this research and development are as follows; (1) The validity of E-Learning is stated to be very valid in terms of content and interest with a total validity value of 84.54%, while the design aspect is stated to be valid with a total value of 85.55% (2) The practicality of E-Learning is based on the lecturer's response after through validation is stated to be quite practical with a total score of 76%, while the practicality of E-learning based on student responses after going through validation is stated to be practical with a total score of 84.12% (3) The effectiveness of E-Learning is effective in improving student learning outcomes as indicated by the number of students who has passed the Minimum Completeness Criteria (87.42%). Based on the findings of this study, it was concluded that E-Learning is valid, practical and effective for use as a learning medium